Novel positron emission tomography imaging targeting cell surface glycans for pancreatic cancer: 18 F ‐labeled rBC2LCN lectin - Kuroda, Yukihito; Oda, Tatsuya; Shimomura, Osamu; Louphrasitthiphol, Pakavarin; Mathis, Bryan J.; Tateno, Hiroaki; Hatano, Kentaro (Cancer science, 2023)
Advancement in early detection modalities will greatly improve the overall prognoses of pancreatic ductal adenocarcinoma (PDAC). For this purpose, we report a novel class of tumor‐specific probes for positron emission tomography (PET) based on targeting cell surface glycans. The PDAC‐targeting ability of rBC2LCN lectin, combined with fluorine‐18 ( 18 F) ([ 18 F]FB‐rBC2LCN), resulted in reproducible, high‐contrast PET imaging of tumors in a PDAC xenograft mouse model. [ 18 F] N ‐succinimidyl‐4‐fluorobenzoate ([ 18 F]SFB) was conjugated to rBC2LCN, and [ 18 F]FB‐rBC2LCN was successfully prepared with a radiochemical purity >95%. Cell binding and uptake revealed that [ 18 F]FB‐rBC2LCN binds to H‐type‐3‐positive Capan‐1 pancreatic cancer cells. As early as 60 min after [ 18 F]FB‐rBC2LCN (0.34 ± 0.15 MBq) injection into the tail vein of nude mice subcutaneously bearing Capan‐1 tumors, tumor uptake was high (6.6 ± 1.8 %ID/g), and the uptake increased over time (8.8 ± 1.9 %ID/g and 11 ± 3.2 %ID/g at 150 and 240 min after injection, respectively). Tumor‐to‐muscle ratios increased over time, up to 19 ± 1.8 at 360 min. High‐contrast PET imaging of tumors relative to background muscle was also achieved as early as 60 min after injection of [ 18 F]FB‐rBC2LCN (0.66 ± 0.12 MBq) and continued to increase up to 240 min. Our 18 F‐labeled rBC2LCN lectin warrants further clinical development to improve the accuracy and sensitivity of early‐stage pancreatic cancer detection.